The integration of PBL and cooperative script to empower critical thinking skills of biology students - Didimus Tanah Boleng; Elsje Theodora Maasawet (University of Muhammadiyah Malang, 2019)
One of the factors lead to the low critical thingking skill is the implementation of teacher center learning. The purpose of this research was to determine the effect of the implementation of Problem-based Learning integrated with Cooperative Script to students’ critical thinking skills. This quasi-experimental research was done in senior high schools of Samarinda, Indonesia. The design used in this research was nonequivalent pretest - posttest control group design. The sample was the class XI students of natural science. The treatment was done in the odd semester in 2016/2017 academic year. The data analysis used was independent-samples t-test (α = 0.05). The results of the data analysis showed that the tvalue (16.57) > ttable (2.00). The mean value of students’ critical thinking skills in the experimental group was 77.28 which means 62% higher than those who were in the control group (47.60). Thus, it can be concluded that the implementation of Problem-based Learning integrated with Cooperative Script gives the significant effect to the students' critical thinking skills.